Integrative multiomics analysis of human atherosclerosis reveals a serum response factor‐driven network associated with intraplaque hemorrhage. Issue 6 (27th June 2021) - Jin, Han; Goossens, Pieter; Juhasz, Peter; Eijgelaar, Wouter; Manca, Marco; Karel, Joël M. H.; Smirnov, Evgueni; Sikkink, Cornelis J. J. M.; Mees, Barend M. E.; Waring, Olivia; van Kuijk, Kim; Fazzi, Gregorio E.; et al.
Abstract: Background: While single‐omics analyses on human atherosclerotic plaque have been very useful to map stage‐ or disease‐related differences in expression, they only partly capture the array of changes in this tissue and suffer from scale‐intrinsic limitations. In order to better identify processes associated with intraplaque hemorrhage and plaque instability, we therefore combined multiple omics into an integrated model. Methods: In this study, we compared protein and gene makeup of low‐ versus high‐risk atherosclerotic lesion segments from carotid endarterectomy patients, as judged from the absence or presence of intraplaque hemorrhage, respectively. Transcriptomic, proteomic, and peptidomic data of this plaque cohort were aggregated and analyzed by DIABLO, an integrative multivariate classification and feature selection method. Results: We identified a protein‐gene associated multiomics model able to segregate stable, nonhemorrhaged from vulnerable, hemorrhaged lesions at high predictive performance (AUC >0.95). The dominant component of this model correlated with αSMA − PDGFRα + fibroblast‐like cell content ( p = 2.4E‐05) and Arg1 + macrophage content ( p = 2.2E‐04) and was driven by serum response factor (SRF), possibly in a megakaryoblastic leukemia‐1/2 (MKL1/2) dependent manner. Gene set overrepresentation analysis on the selected key features of this model pointed to a clear cardiovascular disease signature, with overrepresentation of extracellular matrix synthesis and organization, focal adhesion, and cholesterol metabolism terms, suggestive of the model's relevance for the plaque vulnerability. Finally, we were able to corroborate the predictive power of the selected features in several independent mRNA and proteomic plaque cohorts. Conclusions: In conclusion, our integrative omics study has identified an intraplaque hemorrhage‐associated cardiovascular signature that provides excellent stratification of low‐ from high‐risk carotid artery plaques in several independent cohorts. Further study revealed suppression of an SRF‐regulated disease network, controlling lesion stability, in vulnerable plaque, which can serve as a scaffold for the design of targeted intervention in plaque destabilization. Abstract : This multiomics analysis identified a cardiovascular signature in carotid atherosclerotic lesions, which provides excellent stratification of low‐/high‐risk carotid plaques. This study highlights the advantages of multiomics analysis in terms of model robustness, biological significance, and clinical translatability. The prediction model pointed to an SRF‐regulated disease network providing valuable new insights that expedite the design of targeted intervention in plaque rupture.